2021
DOI: 10.1101/2021.02.06.21251246
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Dynamics of neutralizing antibody responses in acute-phase COVID-19: A potential relationship between disease progression and rapid neutralizing antibody response

Abstract: Introduction Adaptive immunity to severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) dynamics remain largely unknown. The neutralizing antibody (NAb) levels in patients with coronavirus disease 2019 (COVID-19) are helpful for understanding the pathology. Patients and Methods Using SARS-CoV-2 pseudotyped virus, serum sample neutralization values in symptomatic COVID-19 patients were measured using the chemiluminescence reduction neutralization test (CRNT). At least two sequential serum samples collect… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 14 publications
1
1
0
Order By: Relevance
“…The CRNT can assess the inhibitory effect of serum samples on viral attachment and entry into the target cells. As observed in our previous reports (1, 2), the inhibition of the infectivity of sera from symptomatic COVID-19 patients gradually increased during the follow-up period, suggesting that the CRNT reflects the status of immunity acquisition. Meanwhile, commercial antibody tests that do not specify functional antibodies are becoming available.…”
Section: Introductionsupporting
confidence: 83%
See 1 more Smart Citation
“…The CRNT can assess the inhibitory effect of serum samples on viral attachment and entry into the target cells. As observed in our previous reports (1, 2), the inhibition of the infectivity of sera from symptomatic COVID-19 patients gradually increased during the follow-up period, suggesting that the CRNT reflects the status of immunity acquisition. Meanwhile, commercial antibody tests that do not specify functional antibodies are becoming available.…”
Section: Introductionsupporting
confidence: 83%
“…These samples were collected from confirmed COVID-19 patients (n = 74), confirmed non-COVID-19 individuals (n = 179), and unscreened individuals (suspected healthy individuals) (n = 229) ( Table 1 ). Because in our previous study, moderate and severe patients with COVID-19 showed > 50% inhibition (IC 50 ) in the CRNT after day 10 from disease onset (2), the period after day 10 from disease onset was considered as the convalescent phase. Neutralization activity against pseudotyped viruses and anti-RBD antibody levels were evaluated by the CRNT ( Figure 1A ) and quantified by the commercially available test ( Figure 1B ).…”
Section: Resultsmentioning
confidence: 99%